Les nouvelles réalités - Jodoin, Maurice (Assurances, 1985)
In this situational analysis, the author reviews the main problems of the Canadian economy. More specifically, he underlines the necessity of reducing or at least stabilizing the national deficit to preclude the advent of severe problems in a more or less distant future. "The choice is ours, he says, we may be realistic in facing the situation or we may continue in our belief that by asking more, we will necessarily obtain additional benefits at no cost. Governmental services are not free, we must pay for them dearly; the same is true of improved working conditions".